Access to dental services at SUS in adults in the Southern surrounding regions of Federal District, 2010-2011. - Angelo Fonseca SILVA; Margarita Urdaneta URDANETA; Leonor Pacheco SANTOS (Universidade de Brasília, 2015)
Objective: Describe the access to dental services at SUS and oral health indicators in the population living in the Southern surrounding regions of Distrito Federal (Águas Lindas de Goiás, Cristalina, Luziânia, Novo Gama, Santo Antônio do Descoberto e Valparaíso) and the differentials by education and income levels. Method: Population-based household survey, including individuals aged over 18 years (n=605). The sample was selected in three stages. Results: According to the results it can be observed that 76% of the surveyed population does not make use of public dental services SUS using predominantly privately services. Less than half of the population held dental visit in the last 12 months (44.1%). When asked about the reason of not consulting dentist in the past 12 months, 61.2 % of individuals judged not find it necessary to perform regular dental visits. For the population that is in the lower-income strata observed a worse level in oral hygiene e habits. Taking into account the family income it was observed that most individuals who reported never been to the dentist are in the range of less than 2 minimum wages, and individuals with lower education visited the dentist less often. Conclusions: Data from this study show that the population of the Southern surrounding regions the Distrito Federal uses unsatisfactorily public dental services, with evidence of inequalities when taking into account the socioeconomic variables, especially among the lower income families.